The broad-spectrum antibiotic, zeamine, kills the nematode worm Caenorhabditis elegans - Hellberg, Josephine E.; Matilla, Miguel A.; Salmond, George P. (Frontiers in Microbiology, 2015)
Soil bacteria can be prolific producers of secondary metabolites and other biologically active compounds of economic and clinical importance. These natural products are often synthesised by large multi-enzyme complexes such as polyketide synthases (PKSs) or nonribosomal peptide synthases (NRPSs). The plant-associated Gram-negative bacterium, Serratia plymuthica A153, produces several secondary metabolites and is capable of killing the nematode worm Caenorhabditis elegans; a commonly used model for the study of bacterial virulence. In this study, we show that disruption of the hybrid PKS/NRPS zeamine (zmn) gene cluster results in the attenuation of “fast-killing” of C. elegans, indicating that zeamine has nematicidal activity. C. elegans also exhibits age-dependent susceptibility to zeamine, with younger worms being most sensitive to the bioactive molecule. The zmn gene cluster is widely distributed within Serratia and phytopathogenic Dickeya species and investigation of strains harbouring the zmn gene cluster showed that several of them are highly virulent in C. elegans. Zeamine was described previously as a phytotoxin and broad-spectrum antibacterial compound. In addition to its nematicidal properties, we show here that zeamine can also kill Saccharomyces cerevisiae and Schizosaccharomyces pombe. The expression of the zmn gene cluster and regulation of zeamine production were also investigated. Transcription of the cluster was growth phase-dependent, and was modulated by the post-transcriptional RNA chaperone, Hfq. The results of this study show that zeamine is a highly toxic molecule with little, or no, apparent host specificity in very diverse biological systems. In its current form, zeamine(s) may be useful as a lead compound suitable for chemical modification and structure-activity assays. However, because of widespread non-selective toxicity in multiple bioassays, unmodified zeamine(s) is unlikely to be suitable as a therapeutic antibiotic.